2021
DOI: 10.4103/ijdr.ijdr_59_20
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on the Genetic Factors Associated with Skeletal Class II Malocclusion

Abstract: Aim: The aim of this study is to review studies evaluating the role of genetics in skeletal class II malocclusion. Objective: To assess the scientific evidence associating the role of genes in skeletal class II malocclusion. Materials and Methods: A complete search across the electronic database through PubMed, Cochrane, LILACS, BMC and manual hand search of orthodontic journals were done till May 2019. The keywords for the search included: “Genetics”, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…Серед поширених етіологічних чинників є генетичний фактор [2], ротовий тип дихання [3] та інші шкідливі дитячі звички.…”
Section: вступunclassified
“…Серед поширених етіологічних чинників є генетичний фактор [2], ротовий тип дихання [3] та інші шкідливі дитячі звички.…”
Section: вступunclassified
“…Previous studies de ned malocclusion is a complicated disorder produced by the combination of multiple factors, such as genetics, environment, ethnic factors, nonnutritive sucking habits, impaired nasal breathing, and functional atrophy of the maxilla [6, [9][10][11][12]. Several genes were reported earlier and found to be associated with SCIIMO development, including FGFR2, MSX1, MATN1, MYOH1, ACTN3, GHR, KAT6B, HDAC4, and AJUBA [13]. Furthermore, it is suggested that functional alterations, such as temporomandibular disorders (TMD), are more prevalent in SCIIMO [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the genes that contribute to Skeletal Class II malocclusions include ACTN3, GHR, FGFR2, MSX1, MATN1, MYOH1, KAT6B, HDAC4, and AJUBA. [3] Among all the above-mentioned genes, recently more focus has been given to the ACTN3 gene variants which contribute to Skeletal Class II malocclusions in human subjects based on the Sagittal and Vertical dimensions resulting in variation in the facial height proportions caused due to transcription factors controlling muscle morphology. [4] The present review was conducted to highlight the significance of the ACTN3 gene in human masticatory muscle development, especially the masseter muscle and its variations which plays a key role in determining facial height.…”
Section: Introductionmentioning
confidence: 99%